Open Label Observational Comparative Efficacy Study of Ceftriaxone and Levofloxacin in COPD Exacerbations - Sankar, Veintramuthu; Durga, Kanaka; Priya, Krishna; Jose, Sonymol; Joseph, Rinku Mary; Thomas, Pinky Mariyam (Journal of Pharmacy Practice and Community Medicine)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a common preventable and treatable disease. Part of the natural history of the disease is an exacerbation characterized by severity of dyspnoea, increased sputum volume, and purulence. Antibiotics are given to most patients with Acute Exacerbation Chronic Obstructive Pulmonary Disease (AECOPD). Objectives: This study examines the clinical efficacy of ceftriaxone and levofloxacin in patients with AECOPD. It is an open label, observational comparative study. The study compares the efficacy of 1 gm ceftriaxone intravenous infusion BD and oral 500 mg levofloxacin OD for 5 days based on clinical parameters, investigates the healthcare utilization of the study population during hospitalization and looks into the cost comparison between the treatment groups. Methods: The clinical improvement and resolution was measured using the Borg scale for dyspnoea to quantify its severity. The sputum volume and sputum purulence were also quantified by scales. The measurements were done on day 1, 3 and 5. Results: Improvement and resolution of dyspnoea, sputum purulence, and oxygen saturation were similar with empirical intravenous ceftriaxone and oral levofloxacin therapy. Intravenous Ceftriaxone was significantly beneficial with p value of 0.009 in resolving sputum volume compared to levofloxacin. Treatment failure was observed in 23.5% ceftriaxone and 4.5% levofloxacin treatment groups; both were associated with low rate of relapse requiring hospitalization. Among these patients, the time to next exacerbation was within 3 weeks. Conclusion: This study has shown comparable clinical efficacy between ceftriaxone and levofloxacin in AECOPD. The ceftriaxone regimen is certainly costlier than the levofloxacin regimen due to higher acquisition, nursing, and infusion fee.
Keywords: Acute Exacerbation Chronic Obstructive Pulmonary Disease; Ceftriaxone; levofloxacin; Borg scale; Anthonisen criteria